Pertumbuhan Bibit Lada (Piper nigrum L.) pada Media Pembibitan dan Waktu Aplikasi Pupuk NPK - Siti Munawaroh; Niar Nurmauli; S Sugiatno; Rusdi Evizal (Fapetrik-UMPAR, 2020)
The aim of this study was to determine the effect of seeding media, the time difference in NPK fertilizer application, and the responses between the two on the growth of pepper cuttings. The first factor is the composition of the planting medium, consisting of a mixture of river sand + husk charcoal, river sand + compost, husk charcoal + compost, and river sand + husk charcoal + compost. The second factor is the application time of NPK fertilizer (P) which consists of 2, 4, 6, and 8 weeks after planting. The initial condition of the cuttings at the initial fertilization was 2 MSPT, namely the age of 35 DAS. The experiment was repeated 3 times and each experiment consisted of 2 seeds. The homogeneity of the inter-treatment variance used the Bartlett test and the additivity of the data with the Tukey test was followed by an orthogonal comparison test of contrast and polynomial at the ? 5% level. The results showed that the best nursery media for the growth of pepper cuttings were river sand + compost on 4, 8, 12 MSPT leaves, fresh weight, and shoot dry weight. In addition, the time of application of NPK fertilizer to the growth of pepper cuttings did not differ in all observed variables. The results also showed that there was an interaction between the nursery media and the time of NPK fertilizer application on the growth of pepper cuttings. The use of river sand media + husk charcoal was linear with the addition of 1 MSPT NPK fertilizer application time and increased the total number of roots by 2.0 roots. Media sand times + husk charcoal + compost at the time of the optimum application of 5.2 MSPT NPK fertilizer produced the highest number of roots is 18.92 roots.